An OLED-based genosensor for the detection of Hermetia illucens in feeds. (July 2020) - Daniso, Enrico; Melpignano, Patrizia; Tulli, Francesca
Abstract: Recently, the insects meal has been released by the European Union as an ingredient in aquafeeds and only seven insect species have been allowed to be used for these preparations. To avoid misleading results, a suitable method for the detection of these insect species in food/feed, would be highly desirable. In this paper, we present an innovative, sensitive, specific and low-cost Point-of-Care apparatus, based on DNA probes for the detection of one of the most popular insects used in aquafeed preparation, Hermetia illucens ( HI ), commonly known as black soldier fly . The DNA probes adopted for this genosensor have been designed to enable a very specific insect recognition which were derived from DNA primers. The DNA primers were first tested with qPCR. Forty different samples (animal species and common aquafeed ingredients) have been tested to check the possible cross-reactivity, confirming the adequate primers specificity. The primers have been used in a practical application, like the detection of HI in complex matrices of practical aquafeeds. The DNA probes derived by these primers have been then applied to implement an Organic Light Emitting Diode (OLED) based genosensor. The developed genosensor has been tested with HI DNA directly extracted from the insect, without any DNA amplification; a good test sensitivity has been obtained, being 0.75 ng/μl its detection (LOD) limit. Then, the genosensor has been tested with the DNA extracted from the same aquafeeds used in the qPCR experiments. The results obtained by these two methods have then been compared giving very good consistency and both allowed to detect HI meal up to a minimum threshold of 5 g/100gr feed. Highlights: A new DNA method for the identification of the black soldier fly (Hermetia illucens) in feeds. Sensitivity and accuracy of OLED-based Genosensor compared to qPCR. Discrimination among insect species using a new DNA based Genosensor. Hermetia illucens DNA detection in complex matrices.